Do ecological and silvicultural factors influence acorn mass in Holm Oak (southwestern Spain)? - Alejano, R.; Vázquez-Piqué, J.; Carevic, F.; Fernández, M. (Agroforestry Systems, 2011)
The effect of orientation, location, year, and pruning treatment on mean acorn mass in two open woodland experimental locations (Huelva, South-Western Spain) of Holm Oak (Quercus ilex L. subsp. ballota [Desf.] Samp.) was analyzed during 2001–2006. Data were analyzed by using a mixed linear model, where the covariates were tree size parameters (circumference at 80 cm height, crown size), topographic position (wet index and ﬂow length), intraspeciﬁc competition, total acorn crops per tree (weight and number), and climatic parameters. Average estimated acorn mass was 3.17 g acorn -1 in the Calan˜as location and 4.12 g acorn -1 in the San Bartolome´ location, with signiﬁcant differences between locations, among individual trees and across years. Acorns from the south sides of trees were signiﬁcantly heavier than those at other positions. The effect of pruning treatment and the interactions location 9 treatment and treatment 9 year were not signiﬁcant. Our study provides no evidence that pruning affects acorn mass. None of the analyzed covariates related to tree size, topographic position and intraspeciﬁc competition explained the difference among trees, suggesting that heritable factors play an important role. Speciﬁc climatic parameters during September, the most important month for acorn growth, may explain the effects of year and location 9 year on acorn mass. In addition, there appeared to be a ‘‘trade-off’’ between acorn mass and number of acorns.
Keywords: acorn production; Dehesa; Quercus ilex

Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland - Carevic, F. S.; Fernández, M.; Alejano, R.; Vázquez-Piqué, J.; Tapias, R.; Corral, E.; Domingo, J. (Agroforestry Systems, 2009)
Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed signiÞcant differences between the ploughing treatment and the control, and there were also signiÞcant temporal differences. Xylem water potential ranged from- 3.4 ± 0.1 to - 0.7 ± 0.2 MPa, and cuticular transpiration was 62.4Ð 192.9 mmol H2O kg - 1 s - 1 . Acorn production did not differ signiÞcantly according to soil treatment, and showed large intra-speciÞc variability. Individual values ranged from 0 to 1,220 g m - 2 (fresh weight). Positive relationships were found between xylem water potential, cuticular transpiration and relative water content measured at midsummer, and acorn production during the three studied years. These results suggest that climatic conditions and soil water availability have a strong inßuence on plant water status, and therefore on acorn development during summer. The results also reßect the ability of this species to adapt to the Mediterranean climate by preserving water during dry periods, which to a large extent can be attributed to stomatal closure at high relative water content levels, an
Keywords: acorn production; cuticular transpiration; land use; pressure-volume curves; soil treatments; water potential

Influence of pruning and the climatic conditions on acorn production in holm oak (Quercus ilex L.) dehesas in SW Spain - Alejano, R.; Tapias, R.; Fernández, M.; Torres, Enrique; Alaejos, Joaquín; Domingo, Juan (Annals of Forest Science, 2008)
Acorn production by Quercus ilex L. ssp. ballota (Desf.) Samp. in SW Spain was assessed, and variations between years and the inﬂuence of pruning on it were examined. To this end, an experimental study was conducted at two diﬀerent sites (Calañas and San Bartolomé, in the province of Huelva) where trees were subjected to traditional (light, moderate or heavy) pruning and also to a new (crown-regeneration) pruning method. Acorn yield was quantiﬁed over a period of 5 years in the Calañas plot and 4 in the San Bartolomé plot, and found to average at 95.61 ± 0.76 g DM/m2 , which is equivalent to 6.5 ± 0.05 kg DM/tree; however, yield ﬁgures varied markedly between years depending on the particular climatic conditions. The average acorn production was correlated with the water potential in mid summer (end of July); the annual, spring and autumn rainfall; and the actual evapotranspiration for the period from September (previous year) to August. No signiﬁcant diﬀerences in acorn production between traditional pruning intensities were detected; in fact, there were only hints that heavy pruning might result in decreased acorn yields. The new pruning method used, crown-regeneration, seems promising with a view to increasing acorn yield; however, it should be tested on larger sample sizes before any ﬁnal conclusions can be drawn in this respect. Based on the results, the present health status of holm oaks in southwestern Spain (a result of sustained decline) and the low value of ﬁrewood – which used to be a very important source of income from pruning a few decades ago –, the authors recommend reducing the frequency and intensity of pruning in the dehesas of the study area.
Keywords: acorn production; Holm oak; Masting; pruning